HAK ḤIJAB WARIS ANAK PEREMPUAN PERSPEKTIF MAQĀṢID ASY-SYARĪ’AH - Billah, Mu'tashim (Ahkam: Jurnal Hukum Islam, 2021)
This article attempts to analyze the right of the daughter’s heirs to prevent the decedent’s brothers and sisters from getting the inheritance. This article tries to describe comprehensively the rights of daughters in the classical and Indonesia’s fiqh discourse. This is library research that uses available data from books and articles. This article uses a normative-philosophical approach, as well as the theory of the maqāṣid asy-syarī’ah. This article reveals that in certain circumstances, the daughter has the right to deter the decedent’s brothers and sisters in ḥijab ḥirmān way. The opinion of the daughter’s rights to prevent siblings in Islamic inheritance was originally based on the opinion of Ibn ‘Abbas which was later adopted by Shia’s fiqh. This idea, sometimes, was also used by judges of Religious Court in some decisions. In addition, to rely their decision on Ibn ‘Abbas opinion, judges usually refer to the jurisprudence of the Supreme Court (MA). The main argument of this article is based on the expansion and reinterpretation of the meaning of walad that wrote at QS. An-Nisa (4): 11, 12, and 176. Furthermore, this argument could be strengthened by the consideration of maqāṣid’s benchmarks such as illat of law and benefits (maṣlaḥah).